Na ilharga da Fortaleza, logo ali na Beira, lá tem o regatão: os significados dos regatões na vida do Amapá - 1945 a 1970 - Costa, Paulo Marcelo Cambraia da (2007)
Beginning with the naming of the first governor of the Federal Territory of Amapá in 1943, Captain Janary Gentil Nunes, the local style of life was systematically disrespected by that government and by the succeeding governments during the period between 1945 and 1970, stamped by an idea of progress for the region based on a network of highways despite the existing waterways by means of its rivers the dominant facet of life in the region. Such political disdain generated tension between the officially adopted political speech - prioritizing and expanding road construction and the lifestyle of the Amapaenses whose experience and survival were drawn from the rivers. It is within this context that this Master's Dissertation presents a study about the river-water lifestyle and the regatões, the commercializing boat culture that supplied varied goods to the city of Macapá, capital of the Territory. It will demonstrate as well that the rivers were fundamental for the regatões, not only affecting the trading and commercial business, but also in relation to the living experience which transformed itself into the essence of the people of the region. In the study of this specific lifestyle - the regatões, the use of oral documentation in the form of interviews with people directly involved provides evidence of the problematizing of life style of those who anchored their canoes at the Doca do Canal do Igarapé da Fortaleza de São José de Macapá, in opposition to the intention of the territorial governors of building land-based roads. In this manner, a comprehension of the lifestyle of various of the regatão people was undertaken not out of a nostalgic sense of a lost time, but as a means of identifying the tensions and extant contradictions between the governmentally adopted discourse and the ways of life that were occurring facing the changes in the Territory of Amapá at that time